Understanding and addressing gender-based violence: an Australian Indigenous approach. Issue 4 (19th May 2023) - Keddie, Amanda; Delaney, Maria; McVeigh, Ben; Thorpe, Jaylon
ABSTRACT: Addressing the gendered dimensions of family violence is central to preventing violence against women (PVAW). What is seen as more important for Indigenous PVAW programmes, however, is situating gender-based violence within the broader context of colonial violence. In this paper, the significance of this focus is highlighted through a case study of a healing and behavioural change programmefor young Indigenous men within Victoria (Australia). Drawing on the voices of two leading facilitators, the paper examines how this program recognizes and responds to the ongoing impacts of colonisation on the lives of its young Indigenous male participants. It details the significance of safe relations and spaces as requisite for healing the trauma of young Indigenous Australian men towards addressing their perpetuation of gender-based and other forms of violence.